Flu vaccination in elite athletes: A survey among Serie A soccer teams - Signorelli, Carlo; Odone, Anna; Miduri, Alessia; Cella, Paola; Pasquarella, Cesira; Gozzini, Armando; Tamburrino, Pasquale; Castellacci, Enrico (Acta Biomedica Atenei Parmensis, 2016)
Scant data is available on immunization policies and practices among professional athletes. Following up on a recent review on the topic, we conducted a survey among Italian Serie A soccer teams during the influenza season 2015-16, to explore vaccination practices and attitudes as well as influenza vaccine uptake. The survey covered a sample of over 600 professional athletes from 20 teams and was carried out in collaboration with the Italian Association of Physicians of Professional Football Teams (L.A.M.I.CA.). For each team, the head of the medical staff was interviewed (structured telephone interviews, 100% response rate). Seasonal influenza vaccine was actively offered in 75% of Serie A teams with a median coverage rate of 40% (range 0%-100%). Vaccines are often administered after matches or training sessions. We report vaccine hesitancy associated with fear of adverse events, poor communication and other selected determinants. Vaccination in elite athletes, if correctly managed, represents a powerful, cost-effective and long lasting preventive tool. In times where vaccines are losing public confidence, our findings are a useful basis to inform the planning, implementation and evaluation of interventions to promote prevention in sports medicine.